Perioperative hyperglycemia and postoperative periprosthetic joint infection (PJI) after total knee and hip arthroplasty - Yuki Maeda; Nobuo Nakamura; Nobuhiko Sugano (Annals of Musculoskeletal Medicine - Peertechz Publications, 2018)
Background: The quantitative relationship based on infection after total joint arthroplasty and perioperative blood glucose levels are not fully discussed. Hypothesis: The purpose of this study was to find the relationship between peri-operative hyperglycemia and infection after total joint arthroplasty by suggesting a cut-off value over which were the risk factor for postoperative infection. Materials and Methods: A total of 234 patients (209 women, 25 men) who underwent total knee or hip arthroplasty from October 2012 to March 2014 met the inclusion criteria. There were 78 total knee arthroplasty (TKA) and 158 total hip arthroplasty (THA) cases. Of all, 33 had a history of diabetes mellitus (DM). We had followed up for a minimum of 1year postoperatively. The blood glucose levels for two days postoperatively before each meal and the fasting blood glucose (FBG) levels at 1, 2 and 3 weeks after surgery in the morning were measured and compared between the infected and non-infected groups. Results: Higher preoperative HbA1c levels over 7.0 mg/dL, the blood glucose levels at two days over 200 mg/dL, and the FBG levels at one week over 140 mg/dL was higher infection rate after TJA than any other factors. Discussions: FBG levels should be monitored cautiously and we treated tight to maintain the blood glucose level under such cut-offs.